2021
DOI: 10.3390/f12010072
|View full text |Cite
|
Sign up to set email alerts
|

Reforestation or Genetic Disturbance: A Case Study of Pinus thunbergii in the Iki-no-Matsubara Coastal Forest (Japan)

Abstract: In the twentieth century, a substantial decline in Pinus thunbergii populations in Japan occurred due to the outbreak of pine wood nematode (PWN), Burshaphelencus xylophilus. A PWN-P. thunbergii resistant trees-breeding project was developed in the 1980s to provide reforestation materials to minimalize the pest damage within the population. Since climate change can also contribute to PWN outbreaks, an intensive reforestation plan instated without much consideration can impact on the genetic diversity of P. thu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 53 publications
0
1
0
Order By: Relevance
“…What's remarkable is that the genetic patterns of these populations may have persisted over time, even after being introduced from a different cluster. These results strongly support the idea that these individuals were introduced by human activity [7]. Additionally, the genetic structure of EST-SSR markers (Figure 2) revealed a distinct pattern and the presence of a geographic cline.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…What's remarkable is that the genetic patterns of these populations may have persisted over time, even after being introduced from a different cluster. These results strongly support the idea that these individuals were introduced by human activity [7]. Additionally, the genetic structure of EST-SSR markers (Figure 2) revealed a distinct pattern and the presence of a geographic cline.…”
Section: Resultssupporting
confidence: 81%
“…As documented in history, cultivation and domestication of the species have been taking place for centuries [15]. The human involvement has likely influenced the genetic patterns of P. thunbergii populations across Japan [7].In this study, these historical records correspond with the genetic structure findings from EST-SSR markers, especially along the Japan Sea side. The clustering of populations based on EST-SSR markers strongly suggests that human activities have significantly influenced the spread and genetic structure of the species in Japan.…”
Section: Figure 2 K4 Of Reconstructed Genetic Structure Based On Est-...supporting
confidence: 73%
“…They also provide useful information for determining the genetic consequences of tree improvement. Mukasyaf et al [6] revealed the population genetic effects of adding Pinus thunbergii Parl. seedlings from pine wood nematode-resistant stock to existing forests.…”
mentioning
confidence: 99%